Right-Wing Populism and Anti-Gender Movements: The same Coin with Different Faces - KOUROU, NUR SİNEM (My University, 2020)
Populism is one of the outstanding political phenomena in contemporary world politics for the last decade. This is not only about the election triumph of populist parties in several countries, but also it is about the impact of populism as a political strategy to other movements in different contexts. This paper focuses on the link between populism and gender. For this purpose, this paper aims to put one of the salient debates in the 2010s with the relational perspective to understand the new trends on rising right-wing populism and anti-gender movement at the same time. By so doing, this paper analyzes the common triggers of right-wing populism and anti-gender movements to see what makes them coherent. It is then concluded by asking why this relation is a matter while underlining the vulnerable position of women in populist politics.